La calidad del empleo en la población afro-colombiana utilizando índices sintéticos - Jhon James Mora; Lisset Pérez Marulanda; Carlos Giovanni González (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2016)
– This article presents an index of the work quality for Santiago de Cali (Colombia). Our results show that the "comunas" with higher quality are 17, 19, 22 and, 2. "Comunas" 13, 21, 15,3, 7, 20 present poor quality of the work. In this way we show spatiality patterns of the work quality. Also, the fact of being "Afrodescendent" reduces the probability to obtain employments with higher quality and increases the probability to get poor employments.
Keywords: C35; J38; J81; R23; 330; work quality; job satisfaction; synthetics indicators; distance measure; ordered generalized probits